Powder X‐ray diffraction as a powerful tool to exploit in organic electronics: shedding light on the first N, N′, N′′‐trialkyldiindolocarbazole. Issue 2 (12th April 2022) - Vilche, Anna; Bujaldón, Roger; Alcobé, Xavier; Velasco, Dolores; Puigjaner, Cristina
Abstract : The crystal structure determination of N, N ′, N ′′‐tributyldiindolocarbazole from laboratory X‐ray powder diffraction data is fully described. The analysis of the aromatic intermolecular interactions allows the comprehension of this π‐conjugated system, which may have great potential with respect to organic electronics. Abstract : The first crystal structure of a fully N ‐alkylated diindolocarbazole derivative, namely, 5, 8, 14‐tributyldiindolo[3, 2‐ b ;2′, 3′‐ h ]carbazole (1, C36 H39 N3 ), has been determined from laboratory powder X‐ray diffraction (PXRD) data. A complex trigonal structure with a high‐volume unit cell of 12987 Å 3 was found, with a very long a (= b ) [52.8790 (14) Å] and a very short c [5.36308 (13) Å] unit‐cell parameter (hexagonal setting). The detailed analysis of the intermolecular interactions observed in the crystal structure of 1 highlights its potential towards the implementation of this core as a semiconductor in organic thin‐film transistor (OTFT) devices. Since the molecule has a flat configuration reflecting its π‐conjugated system, neighbouring molecules are found to stack atop each other in a slipped parallel fashion via π–π stacking interactions between planes of ca 3.30 Å, with a centroid–centroid distance between the aromatic rings corresponding to the shortest axis of the unit cell ( i.e. c ). The alkylation of the three N atoms proves to be a decisive feature since it favours the presence of C—H…π interactions in all directions, which strengthens the crystal packing. As a whole, PXRD proves to be a valuable option for the resolution of otherwise inaccessible organic crystal structures of interest in different areas.